Incidencia del factor “género” en la producción léxica de los alumnos de ELE de la secundaria en la parte septentrional de Camerún - Zacharie HATOLONG BOHO; Mohamadou AMINOU (Revue Hybrides)
The objective of this article is to study the incidence of the gender in the available lexicon of 959 students who learn Spanish as a foreign language in the northern part of Cameroon, country in which there is an enormous interest in the teaching – learning process of this language. After taking a brief tour of the history of lexical availability, we proceed to the analysis of the production of lexical units in the variable that concerns us in the sample as a whole. The quantitative study of the results obtained allows us to offer statistical data that makes it easier for us to establish a relationship between the aforementioned factor and the lexical competence of these students in the sixteen thematic centers. Thus, this study has allowed us to take position according to which women have a very rich lexical production than men in all thematic fields.